A Pharmacological and Toxicological Profile of Silver as an Antimicrobial Agent in Medical Devices - Alan B. G. Lansdown (Advances in Pharmacological Sciences)
Silver is used widely in wound dressings and medical devices as a broad-spectrum antibiotic. Metallic silver and most inorganic silver compounds ionise in moisture, body fluids, and secretions to release biologically active Ag+. The ion is absorbed into the systemic circulation from the diet and drinking water, by inhalation and through intraparenteral administration. Percutaneous absorption of Ag+ through intact or damaged skin is low. Ag+ binds strongly to metallothionein, albumins, and macroglobulins and is metabolised to all tissues other than the brain and the central nervous system. Silver sulphide or silver selenide precipitates, bound lysosomally in soft tissues, are inert and not associated with an irreversible toxic change. Argyria and argyrosis are the principle effects associated with heavy deposition of insoluble silver precipitates in the dermis and cornea/conjunctiva. Whilst these changes may be profoundly disfiguring and persistent, they are not associated with pathological damage in any tissue. The present paper discusses the mechanisms of absorption and metabolism of silver in the human body, presumed mechanisms of argyria and argyrosis, and the elimination of silver-protein complexes in the bile and urine. Minimum blood silver levels consistent with early signs of argyria or argyrosis are not known. Silver allergy does occur but the extent of the problem is not known. Reference values for silver exposure are discussed.